Registries in systemic sclerosis: a worldwide experience - Galluccio, Felice (2011)
SSc is a multisystem disease characterized by an unpredictable course, high mortality and resistance to therapy. the complexity and severity of SSc is a growing burden on the health-care systems. As a result, researchers are seeking new therapeutic strategies for effectively managing these patients. Disease registries are used to support care management efforts for groups of patients with chronic diseases and are meaningful to capture and track key patient information to assist the physicians in managing patients. for these reasons, SSc surveys, research associations and consortiums are pivotal to conduct ongoing research and data collection to enhance disease knowledge and support research projects. Currently, there are several national SSc registries in the UK, Germany, USA, Canada, Brazil and Australia. There is also an international registry established by the European League Against Rheumatism scleroderma trial and research (EUSTAR) called minimal essential data set (MEDS) Online, which collects data from over 8000 patients from 92 centres worldwide, including 21 European centres and 9 centres outside Europe. By collecting, analysing and disseminating data on disease progression and patient responses to long-term disease management strategies, registries help to improve understanding of the disease and keep medical professionals up to date on the latest advances.